Examining the associations between physical work demands and work injury rates between men and women in Ontario, 1990–2000 - Smith, P (BMJ Group, 2004)
Aims: To describe the decline in injury rates between 1990 and 2000 within occupations stratified across three levels of physical demands and gender, adjusting for industry, in Canada's largest province. Methods: Records of injury compensation claims were obtained from the Ontario Workplace Safety & Insurance Board. The population likely to be insured by the Ontario Workplace Safety & Insurance Board was estimated from Statistics Canada's Labour Force Survey. Injury rates were calculated by three broad levels of physical demands, separately for men and women. Results: Injury rates decreased across each grouping of lower physical demands at work for both men and women, with the largest absolute differences in manual occupational groups (high physical demands). Occupations classified as manual (high physical demands) and mixed (moderate physical demands) showed larger differences in injury rates between genders than did non-manual (low physical demands), although the directions of these differences were not always consistent across different natures of injury classification. Conclusions: The absolute reduction in injury rates in Ontario between 1990 and 2000 was dominated by the reduction in injury rates for men and women in manual and mixed occupations. However, not all types of injury have declined to the same extent. A large proportion of differences in injury rates between men and women can be attributed to the differential labour force participation across occupations and industries, as well as the differential tasks within occupational groups.